The roles of sex and gender in child and adolescent mental health - Martin, Joanna; Hadwin, Julie A. (JCPP advances, 2022)
Neurodevelopmental and mental health disorders are common in children and young people, and frequently continue to be impairing into adulthood. Biological sex and gender identity are important factors in the likelihood of the development, referral and diagnosis of these disorders, as well as sources of clinical heterogeneity. In this editorial, we highlight that the aetiology of neurodevelopmental and mental health disorders in young people is complex and multi‐faceted. Emerging evidence has implicated sex and gender as playing an important role in understanding the onset and course of psychopathology in childhood and adolescence. Here, we underline the significance of continuing to actively study the roles of sex and gender in the context of outlining potential future research directions and understanding how best to support children and young people.